(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Graphene nanoplates, because to their outstanding properties, are finding increasing usage in aerospace engineering. Graphene nanoplates are used in aerospace applications to alleviate problems including lightning strikes, ice accumulation, and other structural impact loads. Adding graphene nanoplates to the wing construction increases its resistance to corrosion. Aircraft wings experience tensile and compressive loads during flight, which may lead to failure before the yield point is reached. In this research, graphene nanoplates are integrated into the wing structure to enhance the structural behaviour of aircraft wings. CATIA is used to simulate the wing’s structure, which is made up of composite materials such ribs, spars, and graphene nanoplates. Deformation, stress, strain, and other mechanical data are shown as a consequence of the tests.